ALGUNOS TREMATODOS DE LAS RATAS DOMESTICAS DE LA CIUDAD DE MEXICO - CERECERO, M CRISTINA (Universidad Nacional Autónoma, Instituto Biología, Laboratorio Helmin, CD MEXICO, DF, MEX, 1946)
The author describes Prosthodendrium paeminosum and P (Paralecithodendrium) tetralobulatum, parasites in the small intestine of Balantiopteryx ochoterenai
ANS INST BIOL
Keywords: TREMATODOS, RATAS DOMESTICAS, CIUDAD DE MEXICO; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; RATAS